Influence of changes on the development of agricultural sector in ukrainian economy (Economics and region, 2018)
The article determines objects of economic changes and their impact on agricultural sector. It has been proven that there is a constant fluctuation in indicators of economic changes in agricultural sector in Ukraine. Sometimes these fluctuations are negative. Being the main food producer in a country for both internal and external consumers, agricultural sector interacts with the external environment through the markets of material and technical resources and agricultural products, public authorities, and other institutional factors. There are external pressures on agricultural sector such as changes in the exchange rate that affect prices for resources and products, bifurcation of the social and political situation etc.
Keywords: agricultural sector; change; macro changes; development; process; movement; environment